Thermo-Gas Dynamics of Hydrogen Combustion and Explosion - Gelfand, Boris E.; Silnikov, Mikhail V.; Medvedev, Sergey P.; Khomik, Sergey V.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The potential of hydrogen as an important future energy source has generated fresh interest in the study of hydrogenous gas mixtures. Indeed, both its high caloricity and reactivity are unique properties, the latter underscoring safety considerations when handling such mixtures.   The present monograph is devoted to the various aspects of hydrogen combustion and explosion processes. In addition to theoretical and phenomenological considerations, this work also collates the results of many experiments from less well known sources. The text reviews the literature in this respect, thereby providing valuable information about the thermo-gas-dynamical parameters of combustion processes for selected experimental settings in a range of scientific and industrial applications.
Critical Combustion Characteristics of Hydrogeneous Mixtures -- Laminar and Cellular Combustion of Hydrogenous Gas Mixtures -- Turbulent Combustion of Hydrogenous Gas Mixtures -- Concentration Limits of Flame Propagation -- Fast Deflagration and Non-Ideal Quasi-Detonation Processes -- Self-Ignition of Hydrogenous Mixtures.-Detonation Combustion Regimes -- Shock-Free and Spontaneous Blast Initiation -- Phenomenology of Hydrogenous Mixtures Explosion -- Blast Pressure Loads Resulted From Hydrogenous Mixture Explosion.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluids; Energy systems; Engineering Thermodynamics, Heat and Mass Transfer; Fluid- and Aerodynamics; Thermodynamics; Energy Systems